2015
DOI: 10.1371/journal.ppat.1004899
|View full text |Cite
|
Sign up to set email alerts
|

A Ribonucleoprotein Complex Protects the Interleukin-6 mRNA from Degradation by Distinct Herpesviral Endonucleases

Abstract: During lytic Kaposi’s sarcoma-associated herpesvirus (KSHV) infection, the viral endonuclease SOX promotes widespread degradation of cytoplasmic messenger RNA (mRNA). However, select mRNAs escape SOX-induced cleavage and remain robustly expressed. Prominent among these is interleukin-6 (IL-6), a growth factor important for survival of KSHV infected B cells. IL-6 escape is notable because it contains a sequence within its 3’ untranslated region (UTR) that can confer protection when transferred to a SOX-targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 86 publications
2
81
0
Order By: Relevance
“…Given that both proteins are also bound by the G-SRE, we evaluated whether they were similarly important for G-SRE-mediated escape. [27] (gray nodes) overlaid with the set of proteins that were also recovered by ChIRP-MS for the IL-6 and GADD45B 3' UTRs (purple nodes) (C) 293T were transfected with the GFP-GADD45B 3'UTR reporter, then 24h later they were subjected to ChIRP analysis and protein samples were western blotted. (D) Crosslinked lysates of 293T cells were subjected to RNA immunoprecipitation (RIP) with control IgG, anti-NCL, or anti-HuR antibodies and the level of co-purifying endogenous GADD45B mRNA was quantified by RT-qPCR.…”
Section: Gadd45b Mrna Is Also Resistant To Sox-induced Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that both proteins are also bound by the G-SRE, we evaluated whether they were similarly important for G-SRE-mediated escape. [27] (gray nodes) overlaid with the set of proteins that were also recovered by ChIRP-MS for the IL-6 and GADD45B 3' UTRs (purple nodes) (C) 293T were transfected with the GFP-GADD45B 3'UTR reporter, then 24h later they were subjected to ChIRP analysis and protein samples were western blotted. (D) Crosslinked lysates of 293T cells were subjected to RNA immunoprecipitation (RIP) with control IgG, anti-NCL, or anti-HuR antibodies and the level of co-purifying endogenous GADD45B mRNA was quantified by RT-qPCR.…”
Section: Gadd45b Mrna Is Also Resistant To Sox-induced Degradationmentioning
confidence: 99%
“…Studying these 'escapees' in aggregate is complicated, however, by the fact that multiple mechanisms can promote apparent escape. These include lack of a targeting motif, indirect transcriptional effects, and active evasion of cleavage [22,[24][25][26][27][28]. This latter phenotype, termed dominant escape, is particularly notable as it involves a specific RNA element whose presence in the 3' UTR of an mRNA protects against SOX cleavage, regardless of whether the RNA contains a targeting motif.…”
Section: Introductionmentioning
confidence: 99%
“…SOX is conserved throughout the herpesvirus family, but only gammaherpesviral SOX homologs display RNase activity in cells (8)(9)(10), and studies indicate that SOX activity is important for the in vivo viral life cycle (11,12). Although SOX targets a degenerate RNA motif present on most mRNAs (13)(14)(15), multiple studies have shown that some transcripts robustly escape SOX-induced decay (16)(17)(18)(19)(20)(21). Studying these "escapees" in aggregate is complicated, however, by the fact that multiple mechanisms can promote apparent escape.…”
mentioning
confidence: 99%
“…These include the lack of a targeting motif, indirect transcriptional effects, and active evasion of ribonucleolytic cleavage (16,(20)(21)(22)(23)(24). The latter phenotype, termed "dominant escape," is particularly notable, as it involves a specific RNA element whose presence in the 3= untranslated region (UTR) of an mRNA protects against SOX cleavage, regardless of whether the RNA contains a targeting motif (19)(20)(21). This protective RNA element was termed SRE (for SOX resistance element), but we recently showed that the SRE is also effective against a broad range of viral endonucleases.…”
mentioning
confidence: 99%
See 1 more Smart Citation